Reactive oxygen species generation in leucocytes of rats under the influence of different concentrations of yttrium gadolinium orthovanadate during oral administration - O.A. Nakonechna; R.O. Bachynskyi; V.V. Miasoiedov; V.O. Vekshyn; M.A. Bondarenko; І.А. Vyshnytska; V.K. Klochkov (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. The use of radiation-modified nanoparticles can lead to higher formation of reactive oxygen species (ROS), which will subsequently lead to greater cytotoxicity and genotoxicity towards tumors. Thus, when using nanomaterials in combination with irradiation, synergism of the effects of factors can be observed.